Between the forest and the sea: hunter-gatherer occupations in the subantarctic forests in Tierra del Fuego (Argentina) - Mansur, Maria Estela; Piqué Huerta, Raquel
Tierra del Fuego is one of the southernmost insular territories of the planet. Hunter-gatherer populations inhabited it since the end of the last glaciation up to the beginning of the twentieth century. Different archaeological sites give testimony of strategies adopted by hunter-gatherers in the occupation of the insular territory. Nevertheless, most of the investigations concentrate on the northern and central steppes and on the southern coasts. The goal of our research is to study the characteristics of human occupation in the central forests. Fieldwork has led to the discovery of archaeological sites in different environments, with a diversity of locations, and a wide functional variability. Besides campsites we have also discovered and studied a ceremonial site. The results summarized here confirm that the subantarctic forest constituted a privileged landscape, rich in different kinds of resources, and intensely exploited by the native populations. Fil: Mansur, Maria Estela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Piqué Huerta, Raquel. Universitat Autònoma de Barcelona; España